Electro-coagulation and electro-oxidation in water and wastewater treatment - Drogui, Patrick; Tyagi, R. D., 1952-; Surampalli, Rao Y.; Zhang, Tian C.; Yan, Song (Sanitary engineer); Zhang, Xiaolei (Sanitary engineer) (American Society of Civil Engineers, 2022)
"This book provides a detailed overview of the origins, principle, benefits, impacts, and applications of electro-coagulation and electro-oxidation for water/wastewater treatment"-- Provided by publisher
Keywords: Water -- Purification -- Coagulation.; Sewage -- Purification -- Oxidation.; Water -- Purification -- Electrochemical treatment.; Sewage -- Purification -- Electrochemical treatment.; Electrocoagulation.; Electrolytic oxidation.; elektronické knihy; electronic books